Project portfolio management in an educational organization - Vera M. Zhurakovskaya; Olga A. Olicheva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper raises the problem of project management in the educational process of a comprehensive school, which ensures the growth of teachers professionalism. The purpose of the paper is to develop a structure for managing a portfolio of projects that ensures the implementation of strategies for educational organization (EО) development, an increase in the professionalism of teachers. The methodological justification for the development of a project portfolio management structure is the theory of project management, the project management methodology Scrum. The research resulted in a developed temporary organizational structure for managing a portfolio of projects in EО. Scientific relevance is the development of a project portfolio management structure in EО from the standpoint of an integrative approach, expressed in the integration of knowledge related to the management of project teams of teachers, the essence of Scrum project management technology, the use of the Trello electronic service, which provides effective management of a project portfolio, including the online mode. The theoretical significance of the solution to the project management problem proposed in the paper is the theoretical positions underlying the description of the temporary organizational structure of project portfolio management, as one of the options for a hybrid structure divisional adhocracy. The practical significance lies in the development of a specific temporary organizational structure for managing club teams of teachers implementing projects in the lyceum in Istra, which can be used in educational practice. An analysis of the results of experimental work on the professional development of teachers of an educational organization through the inclusion of teachers in the implementation of projects related to the solution of professional problems showed a positive dynamics of the levels of teachers professional development. This allowed the authors of the paper to consider the developed pedagogical means of teachers professional development of educational institutions to be effective.